The Order to Sell the Waqf to the Trustee and his Relatives (Journal of Humanities and Social Sciences Research, 2023)
The trustee's and supervisor's possessions in the endowment are bound to comply with the expediency of the endowment and the endowment against them, so whenever it is clear that the sale of the endowment has not been realized and the laws and expediency of the endowment have not been observed in the sale of the endowment, the possessions of the trustee will be invalid. Now the question is, just because the trustee sold the endowment property to himself or his first-degree relatives, can it be said that the interest of the endowment was not respected and the transaction was invalidated? From the point of view of jurisprudence and law, the transactions of the trustee are the same as the transactions of the lawyer, in case of doubt that the trustee of the endowment or the lawyer has complied with expediency, it is necessary to verify the authenticity of all contracts or events created by the former trustee, including the sale of the endowment to himself or His first degree relatives ruled; Unless the new trustee, who has the authority to manage the endowment, can prove its invalidity. In terms of obligation, the trustee can transfer the property of the endowment to himself or his relatives in the assumption of the realization of the sale of the endowment's goods, respecting the envy and benefit of the endowment, although this is frowned upon.